PENERAPAN ZIKIR DALAM MENGATASI KECEMASAN PESERTA DIDIK MELALUI PENDEKATAN CBT (COGNITIVE BEHAVIOR THERAPY) - Arlita, Monica; Putri Rachmawati Wahyuni Asyri Ep; Hartini; Beni Azwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Anxiety issues in students are an important issue in guidance and counseling services because they can affect psychological conditions, social interactions, and academic processes. This study aims to analyze the effectiveness of applying dhikr therapy with a Cognitive Behavioral Therapy (CBT) approach in overcoming student anxiety based on various previous studies. The method used is a literature study by analyzing articles discussing CBT and dhikr therapy in students who experience anxiety. The results of the study indicate that CBT is effective in reducing anxiety through cognitive restructuring that helps individuals change negative thought patterns to be more rational and adaptive. The integration of CBT with dhikr therapy provides more holistic benefits because it adds a spiritual dimension to the intervention process. The techniques used include cognitive restructuring, tawakal (trust), patience, muhasabah (reflection), and repetition of dhikr phrases. The findings show that dhikr helps reduce focus on anxious thoughts, increases emotional calm, strengthens self-control, and develops religious coping. The conclusion of this study shows that the application of dhikr with a CBT approach is effective in overcoming student anxiety through changes in thought patterns, emotional and behavioral control, and strengthening spiritual aspects. The integration of these two approaches can be an alternative for more comprehensive Islamic guidance and counseling services.